1893 Ill. Laws 477-78 - (:unkn) unknown (My University, 1893)
§ 54a: Prohibited the possession, selling, giving, loaning, hiring, bartering, any slung-shot or metallic knuckles, or other deadly weapon of like character. Violators guilty of a misdemeanor, fined not less than ten but no more than two hundred dollars.
Keywords: TRANSFER, MANUFACTURE & POSSESSION